The rhetoric of fiction - Booth, Wayne C. (Chicago, [Illinois] The University of Chicago Press, 1967)
"Rhetoric is the author's term for the means by which the writer makes known his vision to the reader and persuades him of its validity; and he demonstrates convincingly that there is no essential difference between ostentatiously rhetorical novelists like Fielding and Dickens, and the admired masters of impersonality--Flaubert, James, Joyce...this is a major critical work which should be required reading for everyone concerned in the academic study of prose fiction." [Modern Language Review].
Artistic purity and the rhetoric of fiction -- General rules, I: "True novels must be realistic" -- General rules, II: "All authors should be objective" -- General rules, III: "True art ignores the audience" -- General rules, IV: Emotions, beliefs, and the reader's objectivity -- Types of narration -- The authors's voice in fiction -- The uses of reliable commentary -- Telling as showing: dramatized narrators, reliable and unreliable -- Control of distance in Jane Austen's Emma -- Impersonal narration -- The uses of authorial silence -- The price of impersonal narration, I: Confusion of distance -- The price of impersonal narration, II: Henry James and the unreliable narrator -- The morality of impersonal narration.
Includes bibliographical references (pages 399-434) and index.
Keywords: Fiction -- Technique; Fiction -- History and criticism